Strategies to mitigate shrinkage in an intermediate strength self-compacting concrete - Oliveira, M. J. (2021)
Self-compacting concrete (SCC) is a concrete that does not require vibration for casting and consolidation. It is able to flow under its own weight, completely filling the formwork and achieving full consolidation, even in the presence of congested reinforcement. SCC possesses special technical features and properties that recommend its application in a considerable amount of applications. Nevertheless, an inadequate behavior of the material at early ages has been observed in some situations, due to shrinkage. Shrinkage has a significant importance in the design, construction and in-service performance of concrete structures. The regulatory requirements were derived from experience with traditional concrete, which is not always suitable for SCC. In addition, the option of using new materials, such as binders with large amount of pozzolanic or latent hydraulic additions, strongly limits the validity of existing rules. In order to contribute for a better understanding of the major drawback of this material-its high potential shrinkage, experimental research was carried out using different commercial shrinkage-compensating products. This study focuses on the use of a shrinkage reducing admixture and an expansive agent. The results obtained demonstrate the efficiency of the individual or combined use of these products and allowed identifying three different strategies to control the shrinkage, with distinct levels of efficiency.